The Rivers Come: Colonial Flood Control and Knowledge Systems in the Indus Basin, 1840s-1930s. (1st February 2006) - Weil, Benjamin
Abstract : This essay traces the development of the physical and cultural infrastructure of colonial flood control in the Indus valley. Reconstructing investigations into the causes of a series of floods illustrates the conflict between the idiosyncratic, local knowledge-based, approach of generalists and the reductionist, technological mentality of engineers. Repeated attempts to protect towns from the Indus River illustrate the growing dominance during the second half of the nineteenth century of an engineering mentality, despite its practical shortcomings. Complex engineering works replaced traditional warning systems and mobility, undermining alluvial farming systems as well as a precautionary approach to environmental management.